Relationships among M-power, teaching methodology cognitive development, and content achievement. - Purser, Roger K. (My University, 1980)
This investigation used the pretest-posttest control group design to experimentally determine the nature of relationships among M-power, concrete and formal teaching methodologies, cognitive development, and achievement on specified concrete and formal biology concepts. It tested the following null hypotheses: (1) No correlations exist among Biology I students' scores on measures of M-power, cognitive development, or achievement on concrete or formal biology concepts. (2) There are no differences among the mean scores of concretely taught and formally taught Biology I students with regard to M-power, cognitive development, or achievement on concrete or formal biology concepts.

Formal instruction utilizes didactic exposition to efficiently transmit an exhaustive body of concepts. Concrete instruction, however, regularly provides students with numerous concrete objects and experiences in order to stimulate deeper understandings of selected, representative concepts while promoting the development of cognitive processes. Neo-Piagetian theories indicate the size of a subject's working memory, or M-power, is also involved in developing both cognitive processes and understandings of specific concepts.

Cognitive development was measured with three written incidents developed by the Cognitive Analysis Project (CAP) in combination with the Group Embedded Figures Test. The CAP regression equation then generated a single cognitive development score for each student. Instruments measuring content achievement were developed by the investigator. M-power was measured with the 1977 version of the Figural Intersection Test.

Sixty-eight Biology I students were randomly assigned to classes taught concretely. A control group of sixty-seven students were similarly assigned to classes receiving formal instruction of the same content. All students sampled were taking Biology I for the first time and attended at least 80% of the class sessions.

Neither method of instruction was found to enable concrete operational students to achieve substantial understandings of concepts requiring formal operational thought. Nonetheless, calculated t-ratios show the concrete instructional group achieved significantly greater gains (p - .001) in cognitive development than the control group. For this reason, the concrete instruction group exhibited consistently higher achievement on even formal concepts.

After t-ratios indicated M-power development was not significantly affected by instruction, analyses of covariance results indicated that concrete instruction produced significantly greater (p - .001) cognitive development and concrete content achievement than formal instruction, even after statistically controlling any M-power influences. These data suggest the need for regularly providing concrete experiences in the classroom.

Cognitive development and M-power pretests were administered from September 7, 1979 to September 12, 1979. Posttesting for these instruments began May 7, 1980 and ended May 16, 1980. Content examinations were administered immediately following each unit. Since the same content was covered in parallel time frames, content tests were given to both groups on the same days.

Student's t-ratios comparing mean content achievement of the two instruction groups indicated concrete instruction produced significantly greater understandings (p - .001) of concrete concepts on all biology examinations.

At or below the .05 level of significance, positive correlations were found among cognitive development, scores, M-power scores, and achievement on biology content. Coefficients of determination indicted a much stronger relationship between cognitive development and achievement on biology content than that indicated between M-power and content achievement.
Keywords: Education, Sciences.